Molecular Signatures of Human Chronic Atrial Fibrillation in Primary Mitral Regurgitation - Günseli Çubukçuoğlu Deniz; Serkan Durdu; Yeşim Doğan; Esra Erdemli; Hilal Özdağ; Ahmet Ruchan Akar (Cardiovascular Therapeutics)
Objectives. Transcriptomics of atrial fibrillation (AFib) in the setting of chronic primary mitral regurgitation (MR) remains to be characterized. We aimed to compare the gene expression profiles of patients with degenerative MR in AFib and sinus rhythm (SR) for a clearer picture of AFib pathophysiology. Methods. After transcriptomic analysis and bioinformatics (n=59), differentially expressed genes were defined using 1.5-fold change as the threshold. Additionally, independent datasets from GEO were included as meta-analyses. Results. QRT-PCR analysis confirmed that AFib persistence was associated with increased expression molecular changes underlying a transition to heart failure (NPPB, P=0.002; ANGPTL2, P=0.002; IGFBP2, P=0.010), structural remodeling including changes in the extracellular matrix and cellular stress response (COLQ, P=0.003; COMP, P=0.028; DHRS9, P=0.038; CHGB, P=0.038), and cellular stress response (DNAJA4, P=0.038). Furthermore, AFib persistence was associated with decreased expression of the targets of structural remodeling (BMP7, P=0.021) and electrical remodeling (CACNB2, P=0.035; MCOLN3, P=0.035) in both left and right atrial samples. The transmission electron microscopic analysis confirmed ultrastructural atrial remodeling and autophagy in human AFib atrial samples. Conclusions. Atrial cardiomyocyte remodeling in persistent AFib is closely linked to alterations in gene expression profiles compared to SR in patients with primary MR. Study findings may lead to novel therapeutic targets. This trial is registered with ClinicalTrials.gov identifier: NCT00970034.